TLR4 induced TRPM2 mediated neuropathic pain - Mandlem, Venkata Kiran Kumar; Rivera, Ana; Khan, Zaina; Quazi, Sohel H.; Deba, Farah (Frontiers in Pharmacology, 2024)
Ion channels play an important role in mediating pain through signal transduction, regulation, and control of responses, particularly in neuropathic pain. Transient receptor potential channel superfamily plays an important role in cation permeability and cellular signaling. Transient receptor potential channel Melastatin 2 (TRPM2) subfamily regulates Ca 2+ concentration in response to various chemicals and signals from the surrounding environment. TRPM2 has a role in several physiological functions such as cellular osmosis, temperature sensing, cellular proliferation, as well as the manifestation of many disease processes such as pain process, cancer, apoptosis, endothelial dysfunction, angiogenesis, renal and lung fibrosis, and cerebral ischemic stroke. Toll-like Receptor 4 (TLR4) is a critical initiator of the immune response to inflammatory stimuli, particularly those triggered by Lipopolysaccharide (LPS). It activates downstream pathways leading to the production of oxidative molecules and inflammatory cytokines, which are modulated by basal and store-operated calcium ion signaling. The cytokine production and release cause an imbalance of antioxidant enzymes and redox potential in the Endoplasmic Reticulum and mitochondria due to oxidative stress, which results from TLR-4 activation and consequently induces the production of inflammatory cytokines in neuronal cells, exacerbating the pain process.Very few studies have reported the role of TRPM2 and its association with Toll-like receptors in the context of neuropathic pain. However, the molecular mechanism underlying the interaction between TRPM2 and TLR-4 and the quantum of impact in acute and chronic neuropathic pain remains unclear. Understanding the link between TLR-4 and TRPM2 will provide more insights into pain regulation mechanisms for the development of new therapeutic molecules to address neuropathic pain.